Powers and Roles of the Police in the Enforcement of Shariah Offences: (Kuasa dan Peranan Polis dalam Penguatkuasaan Jenayah Syariah) (Kanun: Jurnal Undang-undang Malaysia, 2015)
The police force is the biggest enforcement agency in Malaysia. It is a federal agency. Thus, the question arises as to the extent of the powers of the police force to enforce the shariah. This question arises because the shariah is a state matter. There is no constitutional impediment for the police to enforce the shariah for offences. Similarly, there is no such impediment in the Police Act. Although there is no specific provision for the powers and role of the police in enforcing the shariah, the Police Act contains general provisions for the police to carry out powers as specified by any recognized law. Laws on shariah criminal procedure have made clear provisions concerning the powers and role of the police in enforcing laws on shariah offences.Keywords: police, enforcement, shariah offences, federation, procedure